Radiation Therapy with Concurrent Chemotherapy for Locally Advanced Cervical Carcinoma: Outcome Analysis with Emphasis on the Impact of Treatment Duration on Outcome - Juan Diaz; Daohai Yu; Bizhan Micaily; J. Stuart Ferriss; Enrique Hernandez (Obstetrics and Gynecology International)
Objective. To assess the effectiveness and toxicity of carboplatin concurrent with pelvic external beam radiation and low-dose rate brachytherapy and to assess the impact that adherence to the treatment plan has on outcomes. Methods. Retrospective chart review of 56 patients treated from January 2001 to December 2010. Results. Median follow-up was 68 months. Optimal dose of radiation (ORT) was defined as a minimal cervical dose exceeding 70 Gy, point A dose of 80–90 Gy, and duration not exceeding 56 days. Only 50% received ORT. In multivariable analyses we only found ORT to be statistically significant predictor for progression-free survival (PFS) and overall survival (OS) (HR [95% CI] for non-ORT vs. ORT: 2.4 [1.2, 5.1], P=0.014 for PFS and 2.2 [1.1, 4.6], P=0.035 for OS). The 5-year PFS in patients who received ORT was better than that in patients who received non-ORT, 56% vs. 22% (95% CI: [36%, 72%] vs. [9%, 39%]). Patients who received ORT had a better 5-year OS as well (59% vs. 33%; 95% CI: [38%, 75%] vs. [16%, 51%]). Conclusion. Patients with locally advanced cervical cancer treated with weakly carboplatin or cisplatin, teletherapy, and low dose-dose rate brachytherapy have poorer outcomes when treatment duration is prolonged.